Sensitivity Analysis Of Vynyl Sulphone And BisMonochlorotriazine Reactive Groups Of Reactive Dyes - Sultana, Sanjida; Fatema, Ummul Khair; Islam, Aminul (European Scientific Journal, ESJ, 2016)
Reactive dyes contain different types of reactive groups which have different levels of sensitivity. Reactive dyeing is carried out by exhaust method on cotton knit fabric. A trichromatic combination is chosen containing vinylsulphone and bis-monochlorotriazine reactive groups. Dyeing of fabric is carried out with standard condition and variation of the conditions (electrolyte concentration, pH, exhaustion time, fixation time and M:L). Colorimetric data (DE*) is produced by comparing the difference between standard shade and the resulting shades by using spectrophotometer. Between the investigated reactive groups of reactive dye bismonochlorotriazine shows lower sensitivity in other terms higher robustness than vinyl sulphone.